Toward revealing atomic deformation mechanics in lithium disilicate and β‐quartz containing glass‐ceramics - Deng, Binghui; Harris, Jason T.; Smith, Charlene M.; Luo, Jian (Journal of the American Ceramic Society, 2022)
The mechanics of glass‐ceramics subjected to sharp contact or other loading conditions remain elusive, even after being commercialized in many industrial applications. We present work herein to reveal atomic details of such deformations that are otherwise extremely difficult to probe experimentally for a lithium disilicate (LS2) and β‐quartz containing glass‐ceramics via molecular dynamics simulations. Specifically, the materials are comprised of LS2 and β‐quartz nanocrystals in a residual glass matrix. Regardless of the deformation mechanism, whether it be nanoindentation or crack propagation for samples with pre‐existing flaws, we observe that the LS2 nanocrystal itself undergoes substantial deformation, either by activating dislocations, forming an amorphization zone, or by initiating microcracks at glass‐crystal interfaces or weak crystallographic planes. In contrast, the β‐quartz nanocrystal is not easily deformed and remains almost intact with minimal plastic deformation, thereby forcing shear flow and crack propagation pathways to predominately occur in the residual glass and/or at interfaces. The dramatic difference between the crystalline phases also manifests itself in the deformation mode of interfaces under pure shear loading, in which shear bands preferably occur at the LS2‐glass interfaces, while cavities form at the β‐quartz‐glass interfaces. These observations significantly advance our understanding of glass‐ceramics and pave ways to exploit the understanding for more applications. Comparison of atomic deformation mechanics for glass and glass‐ceramics under nanoindentation and direct crack propagation.